COLLABORATIVE GOVERNANCE IN IMPROVING HEALTH SERVICES FOR DETAINEES IN CLASS IIB SUKADANA DETENTION CENTER - Saputra, Bagas; Santoso, Iman (Universitas Nusa Cendana, 2025)
In Corrections, health services are so important, one of which is the application in the State Detention Center. State detention centers, which are then referred to as Rutan for now in several regions and almost throughout Indonesia, have also switched functions to prisons; this is what then makes Rutan require health services. The purpose of the study was to determine the implementation and obstacles of collaborative governance in improving the health services of prisoners at the Sukadana Class IIB State Detention Center. This study uses a qualitative method with primary and secondary data sources obtained from the Sukadana Class IIB Detention Center. The results of the study, namely Collaborative Governance in Improving the Health Services of Prisoners at the Sukadana Class IIB State Detention Center, have been carried out because they meet the initial conditions, institutional design, informative leadership, and collaboration processes. Keywords: Collaborative Governance; Service; Health; Prisoner